Estradiol and Hyperhomocysteinemia Are Linked Predominantly Through Part Renal Function Indicators - Niu, Xiao Na; Wen, He; Sun, Nan; Yang, Yi; Du, Shi Hong; Xie, Rong; Zhang, Yan Nan; Li, Yan; Hong, Xiu Qin (Frontiers in Endocrinology, 2022)
Background: Previous studies have suggested that estradiol (E2) may affect the metabolism of homocysteine (Hcy) or hyperhomocysteinemia (HHcy). However, the underlying biological mechanisms still remain unclear. We aimed to explore the association between E2 and HHcy in the female population, and to further evaluate the mediating role of renal function indicators. Methods: This unmatched case-control study consisted of 1044 female participants who were 60.60 12.46 years old. Data on general demographic characteristics, such as age, smoking and drinking status, menopause and so on were collected in a personal interview, and laboratory examinations were performed by well-trained personnel. The mediating effect model was applied to analyze the indirect effect of E2 on HHcy. Results: The average levels of Hcy and E2 of the participants was 12.6 mol/L and 14.95 pg/ml. There were statistical differences in renal function indexes and E2 between HHcy group and non-HHcy group. The multiple logistic regression models showed that the renal function index uric acid (UA) was risk factor for HHcy (P < 0.001), and the glomerular filtration rate (GFR) and E2 were protective factors for HHcy (we adjusted BMI, drinking history, smoking history, living area, menopause, education) (P < 0.001). Conclusions: Our findings suggested that UA and GFR mediated the association between E2 and Hcy with 14.63 % and 18.29 %. These data indicated that E2 was a protective factor of HHcy, and the effect of E2 on HHcy may be mediated by renal function indicators UA and GFR.